Fish Identification in The Tanjung Kudu Lake, Kualu Village Tambang District, Kampar Regency, Riau Province - Dwi Azelina Rizki; Ridwan Manda Putra; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractTanjung Kudu lake is an oxbow lake that receive water from the Kampar River during the rainy season. This lake is inhabited by many fish species. However, the information about the type of fish in that area is limited. To understand the types of fish present in the Tanjung Kudu lake, a study has been conducted in August to December 2020. Fish sampling were conducted every day for two weeks until there is no new species found. The fishes were captured using lures, nets and bamboo traps. Fish samples were then identified. Results shown that the caught fish consists of 3 orders, 9 families, 14 genera and 18 species. Among 18 species captured, 9 species were edible fishes and 9 species were ornamental-edible fishes. The water quality of the lake were as follows: temperature of 28oC-29oC, brightness of 45-55 cm, pH of 5-6, dissolved oxygen of 4-4.4 mg/L and carbondioxide 6.18-8.21 mg/L.Keywords: Oxbow lake, Ornamental fish, Edible fishes, Ornamental-edible fishes